Analysis of High Dose and Long-Term Prednisone Therapy on Trap 5B Level Change in Children with Steroid Sensitive Nephrotic Syndrome - Setyani, Dessy Surya; Qibtiyah, Mariyatul; Asmaningsih, Ninik; Yulistiani, Yulistiani (Folia Medica Indonesiana, 2018)
Nephrotic syndrome is a condition which is characterized by protein leakage from the blood to the urine through glomeruli. It leads to hypoproteinemia and generalised oedema. Patients with nephrotic syndrome need high dose and long term glucocorticoid such as prednisone. High dose and long term glucocorticoid can increase bone resorption. Biological marker is a valuable tool to evaluate efficacy of therapy. TRAP 5B is a sensitive biological marker for bone resorption because it reflects the number of osteoclasts. TRAP 5B is not affected by renal dysfunction and food. It also has a low diurnal variation than other bone resorption marker. The aim of this study was to analyze the changes of TRAP 5B levels at induction and alternate phase in children with steroid sensitive nephrotic syndrome. This observational prospective study was conducted from May to October 2016. Venous blood samples obtained at 08.00-10.00 am. TRAP5B levels were measured before and after induction phase and after alternate phase using ELISA. Fifteen patients were included in this study (60% boys). Majority of their age was 6 - <12 years and 40% were dependent steroid NS. TRAP 5B serum levels in induction phase increased by 37.41%±56.22%. In alternate phase, TRAP 5B serum levels increased by 28.75%±66.55% compared to the induction phase. However, the level change of both phases were not significant. As a conclusion, TRAP 5B levels increased in induction and alternate phase after high dose and long-term prednisone treatment in nephrotic syndrome.